An In Vitro Exploration of Interaction Mechanisms of Intracoronal Bleaching on the Compressive Strength of Conventional and Calcium Silicate–Based Self-Adhesive Resins and Their Bonding to Composite Resin Restorative Material - Fereshteh Shafiei; Paria Dehghanian; Shadi Tivay; Yasamin Ghahramani (International Journal of Dentistry)
Conclusions: HP gel deleteriously affected the CS of only TheraCem during nonvital bleaching. The etch-and-rinse mode was preferred in terms of SBS for resin barriers.